Synergistic Antibacterial Activity of Green Gold Nanoparticles and Tannin-Based Derivatives - Elisângela Gomes De Lima Oliveira; Simone Araújo Vieira; Fernando Antônio Gomes Da Silva; Mateus Matiuzzi Da Costa; Anderson S. L. Gomes; Helinando P. De Oliveira (MDPI AG, 2022)
The development of composites with antibacterial activity represents an important strategy to avoid side effects such as increasing bacterial resistance to antibiotics. In particular, the green synthesis of metal nanoparticles avoids the use of hazardous chemical compounds and introduces the intrinsic beneficial properties of plant-derived compounds. Herein, the reduction of gold salt into metal nanoparticles was provided by the action of a cationic polymer derived from tannin (Tanfloc®). Comparative activity of antibacterial agents (pure Tanfloc and Au NPs-Tanfloc) at different concentrations were evaluated in terms of the antibiofilm activity, kill-time assays and inhibition haloes confirming the antibacterial activity of the Tanfloc that is reinforced by the incorporation of reduced gold nanoparticles, resulting in the complete elimination of S. aureus from an initial concentration of 108 CFU/mL after 120 min of reaction of Au NPs + Tanfloc solution in association with strong inhibition of the biofilm formation attributed to the Tanfloc.